Potential for lychee crop in Mata Norte Pernambucana - Brazil | Potencial para cultivo de lichia na Mata Norte Pernambucana - Brasil - Verslype, Nina Iris; Caldas, Raphael Miller de Souza; Machado, José (Revista Geama, 2016)
Lychee crops occurs mainly in South and Southeast regions of Brazil. In this study, the digital terrain modeling (DTM) of the micro-region Mata Norte Pernambucana, was designed to identify the districts that have potential for lychee crop, through the parameters of average altitude, precipitation and temperature. The districts analyzed were Aliança, Buenos Aires, Camutanga, Carpina, Condado, Ferreiros, Goiâna, Itambé, Itaquitinga, Lagoa do Carro, Lagoa do Itaenga, Macaparana, Nazaré da Mata, Paudalho, Timbaúba, Tracunhaém and Vicência. The analysis of climate, wind power and altitude in Mata Norte Pernambucana, has revealed that some districts of the micro-region have potential for lychee crops, which is a product with great financial return, and may contribute to increase economy and quality of life in the micro-region.